PENGARUH PROFITABILITY RATIO DAN CURRENT RATIO TERHADAP HARGA SAHAM PT INDOFOOD SUKSES MAKMUR, TBK PERIODE 2006 – 2011 - Janny Rowena; Hendra Nursalim (Business Management Journal, 2017)
This research was conducted to examine the influence of profitability ratio, current ratio, and debt ratio to PT Indofood Sukses Makmur, Tbk stock price for period 2006 – 2011. Profitability ratios used are ROA (Return on Asset) and NPM (Net Profit Margin). There are four variables : stock price as the dependent variable, while the ROA, NPM, and current ratio as the independent variables. The analysis techniques used in this research is multiple linier regression. Based on statistical t test, NPM have significant influenced on stock price because the significant value is more than 0,05. Based on statistical F test indicates that variables ROA, NPM, and current ratio simultantly affect to Indofood Sukses Makmur, Tbk stock price. Results of coefficient determination test showed that ROA, NPM, and current ratio explained PT Indofood Sukses Makmur, Tbk stock price 92,4% and the rest (7,6%) is influenced by other variables outside the model.Key Words: Profitability ratio, Return on Asset (ROA), Net Profit Margin (NPM)